Comprehensive Review on Hydrogel as Advanced Platform for Novel Drug Delivery Systems - Saurabh V Bodke; Vikrant P. Wankhade; Abhishek D.Mankar; Ishika S. Bijore; Ajay Nemade (Asian Journal of Pharmaceutical Research and Development, 2026)
Hydrogels have emerged as a transformative platform for advanced novel drug delivery systems (NDDS), address ing major limitations of conventional therapeutic administration such as poor localization, uncontrolled release, and systemic toxicity. Their three-dimensional, hydrophilic polymeric network enables exceptional biocompatibility, unable degradability, and controlled drug release kinetics. This review comprehensively explores the fundamental principles, fabrication techniques, and physicochemical properties that govern hydrogel performance in DDS. Special emphasis is placed on stimuli-responsive (smart) hydrogels, including pH-, temperature-, enzyme-, and redox-sensitive systems, which offer precise spatiotemporal control and responsiveness to pathological conditions. The article also highlights biomedicalapplications of hydrogels in oncology, ophthalmology, wound healing, and regenerative medicine, alongside challenges in large-scale manufacturing, regulatory classification, and product standardization. Finally, emerging trends such as hybrid nanocomposite systems and 3D printing are discussed as pivotal strategies for enhancing functionality and facilitating clinical translation. Hydrogels thus represent a cornerstone of next-generation precision drug delivery and personalized medicine.